POLA ASUH ORANG TUA DALAM PEMBENTUKAN AKHLAK ANAK DALAM PENDIDIKAN ISLAM - Mohammad Adnan (CENDEKIA: Jurnal Studi Keislaman, 2018)
Morals can reflect personality as well as can portray characters that if goodness is called good character or noble character, and which contains evil is called bad character or despicable character. Parents always hope for children who are born as descendants of descendants as well as a mandate from Allah SWT, who will become intelligent, pious, and virtuous children, as well as useful for themselves, society and the country. For a long time now, attention to children's lives has always been prioritized, at least from the point of development. The family has an important role in determining the future of the child later, because in the family environment a child also first receives the values and norms that shape his personality later. Basically, the pattern of parenting in a family varies from one family to another. The difference in parenting in the family makes each individual or child have different characteristics or morals in everyday life. In this case all of us can understand that the basic principle of education is something that comes from the family environment. In order for the process of moral formation, so that it can go straight with Islamic education requires serious contributions in shaping the character of children. Then the role of parents is very important and is the most important thing.